Second-hand smoke exposure among school children during COVID-19 in Jeddah - Ahlam A. Mazi, FRCPC (Journal of Taibah University Medical Sciences, 2025)
الملخص: الخلفية: تعرض الأطفال للتدخين السلبي (SHS) يشكل خطرًا على الصحة ويزيد من احتمالية بدء التدخين. على الرغم من أن الأبحاث العالمية حول التدخين السلبي واسعة النطاق، إلا أن الدراسات من السعودية، خاصةً خلال فترات الإغلاق بسبب الجائحة، نادرة. الأهداف: هدفت هذه الدراسة إلى استكشاف أنماط التعرض للتدخين السلبي بين طلاب المدارس خلال جائحة كوفيد-19 في مدينة جدة. كما درست العلاقة بين التعرض للتدخين السلبي وسلوكيات التدخين، بما في ذلك المحاولات، والتدخين الفعلي، والاستعداد للتدخين، وتأثير الأقران. الطرق: تم تنفيذ دراسة مقطعية مدرسية بين سبتمبر وديسمبر 2020 شملت 6717 طالبًا وطالبة تتراوح أعمارهم بين 8 و22 عامًا في جدة. وقد استخدم الاستبيان نسخة معدلة من المسح العالمي لاستخدام التبغ بين الشباب (GYTS)، حيث تم تقييم التعرض للتدخين السلبي في مواقع ومصادر متعددة، ودراسة علاقته بسلوكيات التدخين وتأثير الأقران. النتائج: من بين المشاركين، أفاد 48.8% بتعرضهم للتدخين السلبي بمستويات مختلفة (95% CI: 47.6-50.0%)، وكانت الأماكن الأكثر شيوعًا للتعرض هي الأماكن العامة (33.8%) والمنازل (23.8%). كان التعرض اليومي الأعلى في المنزل (13.4%). شملت العوامل المرتبطة بزيادة التعرض للتدخين السلبي كلاً من التقدم في العمر، الأم العاملة، والحصول على مصروف أسبوعي. كان التعرض للتدخين السلبي مرتبطًا بزيادة خطر التدخين المستقبلي، والتدخين الحالي، والاستعداد للتدخين، وتأثير الأقران، حيث ان التأثير اقوى في حال ارتفاع نسبة التعرض للتدخين السلبي. الخلاصة: أدى التعرض للتدخين السلبي إلى زيادة خطر تجربة التدخين، التدخين الحالي، وزيادة احتمالية التدخين في المستقبل، إضافةً إلى زيادة القابلية للتأثر بتأثير الأقران تجاه التدخين، حيث أظهرت جميع هذه الارتباطات علاقة تعتمد على الجرعة. على الرغم من أن معدلات التعرض مرتفعة، إلا أنها لا تزال مماثلة للبيانات المسجلة قبل الجائحة.تعد هذه النتائج ضرورية لتطوير استراتيجيات للحد من التعرض للتدخين السلبي، ومنع بدء التدخين بين طلاب المدارس، وتعزيز صحتهم العامة. Abstract: Background: Second-hand smoke (SHS) exposure among children leads to significant health risks and increases the likelihood of smoking initiation. Global research into SHS is extensive but very few studies have been conducted in KSA, especially during pandemic lockdowns. Objectives: This study explored the patterns of SHS exposure among school-age children during the COVID-19 pandemic in Jeddah, KSA. The relationships of SHS with smoking behaviors were also examined, including attempts, active smoking, willingness to smoke, and peer influence. Methods: A cross-sectional school-based survey was conducted from September to December during 2020 among 6,717 children in Jeddah, aged 8–22 years. The survey, adapted from the Global Youth Tobacco Survey, assessed self-reported SHS exposure across various locations and sources, and its correlations with smoking behaviors and peer influence. Results: Among the participants, 48.8 % reported exposure to SHS at varying levels (95 % confidence interval: 47.6–50.0 %), where the most common exposure sites were public places (33.8 %) and homes (23.8 %). Daily exposure was highest at home (13.4 %). Independent factors associated with SHS exposure included older age, maternal employment, and receipt of weekly pocket money. Furthermore, SHS exposure was positively correlated with a higher risk of ever smoking, current smoking, and future willingness to smoke, as well as peer influence in an independent relationship, with stronger effects at higher exposure levels. Conclusion: Despite the pandemic lockdown, exposure to SHS remained high among children in Jeddah, and it was consistent with pre-pandemic levels. These findings highlight the need for targeted strategies to reduce SHS exposure and prevent smoking initiation, contributing to better health outcomes for children.